We know the derivative of secx, which is secxtanx.
(secx)' = secxtanx
We can find the derivative of sec(√x) using chain rule.
If y = sec(√x), find ᵈʸ⁄dₓ.
y = sec(√x)
Let u = √x.
Then, we have
y = secu
Now, y = secu and u = √x. That is, y is a function of u and u is a function of x.
By chain rule, the derivative of y with respect to x,
Substitute y = secu and u = √x.
Substitute u = √x.
Kindly mail your feedback to firstname.lastname@example.org
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
May 26, 23 12:27 PM
May 21, 23 07:40 PM
May 20, 23 10:53 PM